Implementasi Program Skrining Hipotiroid Kongenital (HKI) pada Bayi Baru Lahir di Kabupaten Jember - Margareta, Ana Silfia (STIKES Yayasan RS.Dr.Soetomo, 2025)
Congenital hypothyroidism has a serious impact on cognitive and physical development if not detected and treated promptly. Most cases are permanent and result in adverse effects. This study aims to determine the success of the implementation of Congenital Hypothyroidism (CHS) screening in Jember Regency. This type of research is qualitative with an in-depth interview design. The objects in this study were 13 informants and 1 triangulation informant. This research was conducted in Jember Regency in August 2024. The instrument used was an in-depth interview guide. Data analysis used data reduction. The results of the study showed that the SHK program had been implemented in accordance with the policy, but the achievement of SHK implementation was still low. This is influenced by factors of human resources, funding sources, inadequate facilities and infrastructure. It is recommended that there is a need for integration of the implementation of other programs that can support the SHK program with the same goal, namely early detection of congenital hypothyroidism in newborns